2004
DOI: 10.1097/00001756-200403220-00032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sleep on auditory learning: a behavioral study

Abstract: Evidence continues to support a role for sleep in delayed learning without further practice. Here we demonstrate the beneficial influence of sleep on auditory skill learning. Fifty-six subjects were randomly assigned to two groups, trained and tested on a pitch memory task three times across 24 h. The morning group was trained at 09.00 h, retested 12 h later that same day, and again after 12 h sleep. The evening group was trained at 21.00 h, retested 12 h immediately after sleep, and again 12 h later the next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 18 publications
2
40
0
3
Order By: Relevance
“…Evidence of sleep-dependent skill learning has now been demonstrated across a wide variety of skill domains, including the visual (Karni et al, 1994;Gais et al, 2000;Stickgold et al, 2000), auditory (Atienza et al, 2004;Gaab et al, 2004), and motor (Smith and MacNeill, 1994;Fischer et al, 2002;Walker et al, 2002Walker et al, , 2003Kuriyama et al, 2004) systems. Specifically, sleep has been implicated in the ongoing process of consolidation after initial acquisition, whereby delayed learning could occur in the absence of further practice (Smith, 1995;Stickgold et al, 2001;Walker and Stickgold, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of sleep-dependent skill learning has now been demonstrated across a wide variety of skill domains, including the visual (Karni et al, 1994;Gais et al, 2000;Stickgold et al, 2000), auditory (Atienza et al, 2004;Gaab et al, 2004), and motor (Smith and MacNeill, 1994;Fischer et al, 2002;Walker et al, 2002Walker et al, , 2003Kuriyama et al, 2004) systems. Specifically, sleep has been implicated in the ongoing process of consolidation after initial acquisition, whereby delayed learning could occur in the absence of further practice (Smith, 1995;Stickgold et al, 2001;Walker and Stickgold, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrations of overnight, sleep-dependent learning have now been reported across both sensory (Karni et al, 1994;Gais et al, 2000;Stickgold et al, 2000a,b;Fenn et al, 2003;Atienza et al, 2004;Gaab et al, 2004) and motor (Smith and MacNeill, 1994;Fischer et al, 2002;Walker et al, 2002Walker et al, , 2003aKorman et al, 2003;Huber et al, 2004;Robertson et al, 2004;Kuriyama et al, 2004) skill memory domains.…”
mentioning
confidence: 98%
“…Demonstrations of overnight, sleep-dependent learning have now been reported across both sensory (Karni et al, 1994;Gais et al, 2000; Stickgold et al, 2000a,b;Fenn et al, 2003;Atienza et al, 2004;Gaab et al, 2004) Regarding motor-sequence learning, Walker et al (2002, 2003a,b) have shown that a night of sleep can trigger significant improvements in both performance speed and accuracy on a finger-tapping task, while equivalent periods of time awake do not result in any such learning enhancements. Furthermore, these overnight learning gains correlated with the amount of stage two non-rapid eye movement (NREM) sleep, particularly late in the night (Walker et al, 2002).…”
mentioning
confidence: 99%
“…Commentaries by Schredl, Smith, and Doyon, Carrier, Simard, Tahar, Morin, Benali, & Ungerleider (Doyon et al) all address a point of importance often overlooked by those who deny the role of sleep in memory processing. Although delayed overnight improvement appears to occur robustly and consistently across a wide variety of procedural tasks in the motor (Fischer et al 2002;Maquet et al 2003;Robertson et al 2004;Smith & MacNeill 1994;Walker et al 2002;2003a;2003b), visual (Gais et al 2000;Karni et al 1994;Mednick et al 2002;Stickgold et al 2000a;2000b), and auditory (Gaab et al 2004) domains, they do not all show a relationship with the same stage of sleep. For the naysayer, this has been taken as evidence against the role of sleep in memory processing stages.…”
Section: R2 Memory Systems and Forms Of Learningmentioning
confidence: 99%